1973
DOI: 10.1068/p020287
|View full text |Cite
|
Sign up to set email alerts
|

The Autonomy of Visual Kinaesthesis

Abstract: Kinaesthesis, the sensing of body movement, which is essential for controlling activity, depends on registering the changes which accompany body movement. While there are two basic types of change—mechanical (articular, cutaneous, and vestibular) and visual—and so two potential sources of kinaesthetic information, the mechanical changes have traditionally been considered the basis of kinaesthesis, vision being considered a purely exteroceptive sense. J.J. Gibson, on the other hand, has argued that vision is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
191
0
9

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(209 citation statements)
references
References 4 publications
9
191
0
9
Order By: Relevance
“…For example, self movement in the light produces global optical flow information that strongly and effectively signals to observers a change in position in the world (via visual proprioception; Gibson, 1966;Lee & Aronson, 1974;Lee & Lishman, 1977;Lishman & Lee, 1973) and specifies the actual direction in which one is heading (e.g., Cutting, 1986;Lee, 1993;Warren &Hannon, 1988;Warren, Mestre, Blackwell, & Morris, 1991;Warren, Morris, & Kalish, 1988). This percept of self movement is reinforced by the body movement--primarily vestibular system information that similarly signals a change in position as well as a rotational path through the world.…”
Section: Discussionmentioning
confidence: 99%
“…For example, self movement in the light produces global optical flow information that strongly and effectively signals to observers a change in position in the world (via visual proprioception; Gibson, 1966;Lee & Aronson, 1974;Lee & Lishman, 1977;Lishman & Lee, 1973) and specifies the actual direction in which one is heading (e.g., Cutting, 1986;Lee, 1993;Warren &Hannon, 1988;Warren, Mestre, Blackwell, & Morris, 1991;Warren, Morris, & Kalish, 1988). This percept of self movement is reinforced by the body movement--primarily vestibular system information that similarly signals a change in position as well as a rotational path through the world.…”
Section: Discussionmentioning
confidence: 99%
“…This is demonstrated by the fact that compelling illusions of self-motion can be induced by visual information alone. For example, when subjects are placed in a "swinging room," where the walls and ceiling swing back and forth, they soon experience the illusion that they themselves are swaying (Lee & Aronson, 1974;Lee & Lishman, 1975;Lishman & Lee, 1973). Similarly, when subjects are placed inside a "rotating drum," a rotating cylinder with a patterned inner wall, they quickly experience an illusion of self-rotation (Brandt, Dichgans, & Koenig, 1973;Mach, 1875).…”
mentioning
confidence: 99%
“…Other experiments have demonstrated that observers can recognize their own egomotion (Lee & Aronson, 1974;Lee & Lishman, 1975;Lishman & Lee, 1973;Warren, 1976) or the translation in depth of external objects (Borjesson & von Hofsten, 1972, 1973Johansson, 1950Johansson, , 1964Schiff, 1965). There is also evidence that observers can recognize more complicated rigid motions such as rotation about an axis that is translating (Duncker, 1929(Duncker, /1937Johansson, 1964Johansson, , 1973Johansson, , 1974aProffitt, Cutting, & Stier, 1979) or rotating (Johansson, 1958(Johansson, , 1974bRubin, 1927).…”
mentioning
confidence: 99%